Developing Pop Up Books As Learning Media to Teach Reading Comprehension at Senior High School Bangun Cipta Rumbia - Saputra, Dicky Abdul Wahyu; Zuniati, Mai; Hasyim, Umar Al Faruq A; Suhono, Suhono; Irhammudin, Irhammudin; Sari, Yeasy Agustina (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The article aims to develop a learning media product in the form of pop up book media for reading comprehension in English, which is specifically designed for grade 10 students at Bangun Cipta Rumbia Senior High School. This research uses the RnD (Research and Development) method, with the ADDIE development model, namely analysis, design, development, implementation and evaluation. Based on assessments carried out using validity tests by experts, it shows that the product is suitable for use. The results of the validity test by media experts got a score of 92.5%, while the results of the validity test by material experts got a score of 95.0%, including the very decent category, and the results of the student response questionnaire got a score of 90.4% in the very good category. Based on these results, it can be concluded that pop up book media can improve the reading comprehension skills of grade 10 students. Pop-up books serve as a unique blend of art and education, offering a wealth of advantages that elevate the learning experience. By introducing elements of movement and animation, they transform reading from a static task into an interactive journey, sparking curiosity and keeping students engaged. As a result, pop-up books can help learners overcome obstacles in absorbing new material.